2020
DOI: 10.1108/ijoa-04-2020-2139
|View full text |Cite
|
Sign up to set email alerts
|

Graduating students’ standpoints on Wasta as a ‘gateway’ to employment: motives and influences

Abstract: Purpose This study aims to uncover graduating students’ standpoints on Wasta through exploring their motives to use it and its potential influences on them particularly when they move to a workplace (i.e. after leveraging it to gain employment). Design/methodology/approach Semi-structured interviews were conducted with 26 graduating students studying at a Jordanian private university. Findings Graduating students considered Wasta as a gateway to employment, which rationalised their motives to use it in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Some specialists even went so far as to coin it as a way of life (Al‐Ramahi, 2008; Cunningham & Sarayrah, 1993; Hutchings & Weir, 2006b). Thus, it comes as no shock that Arab nationals are quite used to resorting to wasta when it comes to any HRM practice, most notably recruitment and promotion (Afiouni, Ruël, & Schuler, 2014; Aladwan, Bhanugopan, & Fish, 2014; Alsarhan, 2021; Al‐Twal, 2022; Al‐Twal & Aladwan, 2021; Branine & Analoui, 2006; Budhwar & Mellahi, 2006; El‐Said & McDonald, 2001; Ezzedeen & Swiercz, 2001; Harbi, Thursfield, & Bright, 2017; Hutchings & Weir, 2006b; Loewe et al, 2008; Mohamed & Mohamad, 2011; Mohammad & Darwish, 2022; Sfeir, 2022; Tlaiss & Elamin, 2016; Tlaiss & Kauser, 2011; Valax & Alsarhan, 2021). Hence the difficulty to challenge the status quo, as many individuals (and even families and tribes) who benefit from the prevalence of wasta are not likely to be eager to give up their gains and privileges (Ta'Amnha et al, 2016).…”
Section: The Conditions Of Success Of Change Management Against Wastamentioning
confidence: 99%
“…Some specialists even went so far as to coin it as a way of life (Al‐Ramahi, 2008; Cunningham & Sarayrah, 1993; Hutchings & Weir, 2006b). Thus, it comes as no shock that Arab nationals are quite used to resorting to wasta when it comes to any HRM practice, most notably recruitment and promotion (Afiouni, Ruël, & Schuler, 2014; Aladwan, Bhanugopan, & Fish, 2014; Alsarhan, 2021; Al‐Twal, 2022; Al‐Twal & Aladwan, 2021; Branine & Analoui, 2006; Budhwar & Mellahi, 2006; El‐Said & McDonald, 2001; Ezzedeen & Swiercz, 2001; Harbi, Thursfield, & Bright, 2017; Hutchings & Weir, 2006b; Loewe et al, 2008; Mohamed & Mohamad, 2011; Mohammad & Darwish, 2022; Sfeir, 2022; Tlaiss & Elamin, 2016; Tlaiss & Kauser, 2011; Valax & Alsarhan, 2021). Hence the difficulty to challenge the status quo, as many individuals (and even families and tribes) who benefit from the prevalence of wasta are not likely to be eager to give up their gains and privileges (Ta'Amnha et al, 2016).…”
Section: The Conditions Of Success Of Change Management Against Wastamentioning
confidence: 99%
“…There is, however, a paucity of research, which resulted in a limited theoretical rigor and disjointed understanding of various aspects of wasta . This includes, for example, perceptions of wasta (Aldossari & Robertson, 2016; Barnett et al, 2013), the role of the type of network in explaining how wasta works (Ali & Weir, 2020), individuals' motives to get engaged in it and the influence it has on the donor and the receiver (Al‐Twal & Aladwan, 2020; Kropf & Newbury‐Smith, 2016).…”
Section: What Is Wasta?mentioning
confidence: 99%
“…Another study conducted by Kilani and Sakijha (2002) in Jordan found that 90% of surveyed people admitted that they would use wasta , although 87% revealed that they want it to be eradicated; this alludes to the pain and paradox of wasta , as described by Cunningham and Sarayrah (1993). Similarly, a study conducted by Al‐Twal and Aladwan (2020) to explore graduating students' standpoints of wasta as a gateway to employment uncovered paradoxical views in this sense. Students accepted and justified wasta for personal use, yet rejected it when it comes to others.…”
Section: Rationale For Using Narrative Inquiry In Wasta Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…People use Wasta for different reasons, and the outcomes of using it could be positive or negative for individuals and organizations alike (Aldossari & Robertson, 2016; Alsarhan & Valax, 2020; Al‐Ma'aytah et al., 2021; Ali & Weir, 2019; Al‐Twal & Aladwan, 2021; Andrews, 2017; Barnett et al., 2013). For this reason, the manifestations of Wasta vary (Berger et al., 2019), especially with the existence of various controllable and uncontrollable justifications for its use (Al‐Twal & Aladwan, 2021).…”
Section: Introductionmentioning
confidence: 99%